Pemanfaatan dan Perburuan Gajah di Perkebunan Sumatra Timur pada Awal Abad XX - Suriani, Suriani (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2023)
This paper aims to narrate the presence of elephants in the history of plantations in East Sumatra in the process of opening and building infrastructure. It used historical method with primary sources the photographs of the use and hunting of elephants in East Sumatra in the early 20th century, East Sumatra plantation archives from their opening until their development in the early 20th century, newspapers and the Staatsblad of 1924 and 1931. Elephants played an important role in the the process of land clearingand infrastructure development in plantations in East Sumatra, but in the second decade of the XX century, hunting of elephants was still carried out. At that time elephants were needed for development as well as for fun in the form of hunting. The Colonial Government passed laws on hunting and protecting wild animals to minimize them. Based on these facts, in the history of plantations in East Sumatra there are not only narratives of capitalism, coolies or social history that discuss social segregation, but there are also narratives about environmental history that expose changes in the landscape of East Sumatra and the exploitation of elephants.